Establishment of physicochemical measurements of water polluting substances via flow perturbation gas chromatography - Mohammad, H.H.; Sharifuddin Mohd Zain; Rashid Atta Khan; Khalisanni Khalid (Universiti Kebangsaan Malaysia, 2014)
Spillage of water polluting substances via industrial disaster may cause pollution to our environment. Thus, reversed-flow gas chromatography (RF-GC) technique, which applies flow perturbation gas chromatography, was used to investigate the evaporation and estimate the diffusion coefficients of liquid pollutants. Selected alcohols (99.9% purity) and its mixtures were used as samples. The evaporating liquids (stationary phase) were carried out by carrier gas-nitrogen, 99.9% purity (mobile phase) to the detector. The findings of this work showed the physicochemical measurements may vary depending on the composition of water and alcohol mixtures, temperature of the mixtures, as well as the types of alcohol used. This study implies that there is a variation in the results based on the concentration, types and temperature of the liquids that may contribute in the references for future research in the area of environmental pollution analysis.